Cost and Time Performance Analysis with Concept of Earned Value (Case Study Jakarta - Cikampek II Elevated Project) - Noviawati Puspita; Yopi Lutfiansyah (LPPM NAROTAMA UNIVERSITY, Indonesia, 2020)
The research procedure starts with conducting a literature study, collecting data, and summarizing the results of gathering existing data. The purpose of this study is to evaluate the deviation of costs and time, calculate the estimated cost and time needed to complete the project work, calculate the estimated profit or loss that may occur in the completion of the project. Variants emphasized here are to investigate deviations in costs or planned schedules that have been planned or determined. The results of the analysis in Jakarta-Cikampek II Elevated Project stated that in July 2019 the SPI value was 0.96 <1 which could be interpreted that the project progress had been delayed and the CPI value was 1.44> 1 which could be interpreted that the actual the project cost is still smaller than the total budget cost. Estimated total costs up to the end of the project in the amount of Rp.2,694,413,965,781 of the total budget cost of Rp. 3,872,143,387,752 can save Rp.1,177,729,421,971. As for the estimated time to finish until the end of the project which is for 918 days from the time of the 915 day contract, there will be a delay of 3 days.